A harmonious encoding of instrument values by a nineteenth-century Parisian violin dealer. Issue 5 (3rd September 2017) - Échard, Jean-Philippe; Gaudry, Pierrick
ABSTRACT: The study of three ledgers from the archives of a prominent Parisian violin maker's workshop (active from 1796 to 1948) reveals that some of their content was encrypted. Presented here are the deciphering of the code and a discussion of its use in the context of the workshop. Charles-Adolphe Gand introduced this code around 1847 to encrypt values of antique/used violins he would buy and resell. His successors maintained the use of this code at least until 1921. Taking a few examples of instruments by Stradivari and other violin makers, researchers illustrate how the decoded ledgers (listing transactions for more than 2, 500 instruments) are of high interest as historical sources documenting the margins, rebates, and commercial practices of these violin dealers. More generally, this article will contribute to better describing the evolution of the market for antique instruments of the violin family.